RANCANG BANGUN ALAT PERAJANG SINGKONG DAN PISANG DENGAN MOTOR PENDORONG - Fifiningrum, Fifiningrum; Wirdha, Wirdha; Widya Ningsih, Sari; Kumara, Dody Chandra (Foristek, 2022)
Chips are a type of snack or snack made from tubers such as cassava and bananas which are usually produced by home businesses. However, most home-based chips making businesses still use manual tools such as kitchen knives or cutters so that production takes longer, the thickness cannot be adjusted and the risk of workers' hands being injured by knives is added. This cassava and banana chopper uses a driving motor system that is driven by an electric motor with a speed of 1400 RPM HP and the pusher is driven by a power window. The results of this tool chopping obtained thickness in cassava and banana is 1-1.5 mm which is the standard thickness of chips in general. In addition, the results obtained are faster production compared to manual techniques using a kitchen knife or cutter. The conclusion is that the cassava and banana chopper with a driving motor is very efficient for chip craftsme, because the production time is faster and the thickness of the cassava and banana slices is uniform, namely 1-1.5 mm.